2002
DOI: 10.1074/jbc.m112429200
|View full text |Cite
|
Sign up to set email alerts
|

Similar Structural Basis for Membrane Localization and Protein Priming by an RNA-dependent RNA Polymerase

Abstract: Protein primers are used to initiate genomic synthesis of several RNA and DNA viruses, although the structural details of the primer-polymerase interactions are not yet known. Poliovirus polymerase binds with high affinity to the membrane-bound viral protein 3AB but uridylylates only the smaller peptide 3B in vitro. Mutational analysis of the polymerase identified four surface residues on the three-dimensional structure of poliovirus polymerase whose wild-type identity is required for 3AB binding. These mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
112
1
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(120 citation statements)
references
References 47 publications
5
112
1
2
Order By: Relevance
“…Depending on the virus, replication may occur on rearranged convoluted membranes, single or double membrane vesicles of various sizes derived from the endoplasmic reticulum (ER), the intermediate compartment between the ER and the Golgi apparatus, the trans-Golgi network, mitochondria or even lysosomes (Miller & KrijnseLocker, 2008). These membrane structures induced by positive-strand RNA viruses probably serve as a scaffold for the assembly of viral replication complexes by providing an organization and environment facilitating viral replication (Lyle et al, 2002;Schwartz et al, 2002). Some positivestranded RNA viruses including some strains of poliovirus (Jackson et al, 2005), coxsackievirus B3 (Wong et al, 2008), dengue virus (Lee et al, 2008) and mouse hepatitis coronavirus (Prentice et al, 2004) may take over the host autophagy machinery to facilitate their own replication.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the virus, replication may occur on rearranged convoluted membranes, single or double membrane vesicles of various sizes derived from the endoplasmic reticulum (ER), the intermediate compartment between the ER and the Golgi apparatus, the trans-Golgi network, mitochondria or even lysosomes (Miller & KrijnseLocker, 2008). These membrane structures induced by positive-strand RNA viruses probably serve as a scaffold for the assembly of viral replication complexes by providing an organization and environment facilitating viral replication (Lyle et al, 2002;Schwartz et al, 2002). Some positivestranded RNA viruses including some strains of poliovirus (Jackson et al, 2005), coxsackievirus B3 (Wong et al, 2008), dengue virus (Lee et al, 2008) and mouse hepatitis coronavirus (Prentice et al, 2004) may take over the host autophagy machinery to facilitate their own replication.…”
Section: Introductionmentioning
confidence: 99%
“…Yeast two hybrid and biochemical analyses have indicated that the 3AB protein strongly interacts with 3D pol and the sequences primarily responsible for this interaction are located in the 3B domain of the protein (9,11). Four amino acids in a hydrophobic patch on the surface of 3D pol were recently identified as binding partners of 3AB (8). Protein 3AB also has the propensity to dimerize and form higher oligomers in solution in the absence of detergent.…”
mentioning
confidence: 99%
“…Some of the viral nonstructural proteins (2B, 2C ATPase and 3A) associate with the replication complex via their own membrane binding domains while others are recruited to the complex by protein/protein or protein/RNA interactions (1,7). The PV RNA polymerase 3D pol is an example of a soluble protein that interacts with another protein, 3AB, whose hydrophobic domain, located in 3A, anchors the complex to membranes (8,9). 3AB is a small basic protein that contains a hydrophobic and membrane-binding region near the C-terminus of its 3A domain.…”
mentioning
confidence: 99%
“…This is particularly evident with the less-active serotype O enzyme. The addition of ZnCl 2 (60 M) to enhance the activity according to previously reported PV protocols (2,8,9,12,21) had little effect. Using a similar assay, we showed that the D388A mutant was unable to incorporate [ 32 P]UTP, as expected (Fig.…”
mentioning
confidence: 99%